Peran Unit TOC (Terminal Operation Center) Dalam Meningkatkan Kinerja Pelayanan Area Check-In Terminal 3 Domestik Bandar Udara Internasional Soekarno-Hatta Tangerang - Rizaldi Ardin Wicaksono (Lembaga Pengembangan Kinerja Dosen, 2023)
The Terminal Operation Center (TOC) unit is an integrated monitoring system for airport operations and service activities at the terminal, using the concept of collaboration with other stakeholders. This study discusses the Terminal Operation Center (TOC) Unit in supervising the operational performance and service of check-in area facilities at Domestic Terminal 3 at Soekarno Hatta International Airport, Tangerang. The check-in area is a place that must always be monitored because it is the initial gathering point for flight service users who have the potential for queue accumulation.During the months of August and September 2022, this study was carried out at Tangerang's Soekarno Hatta International Airport. The data collection techniques employed were observation, interviews, literature and documentary studies, and descriptive qualitative research. Data collection, data reduction, data presentation, and findings were all assessed utilizing qualitative data analysis methodologies, and their validity was checked by using three different sources and three different methods.The results of this study indicate that at Soekarno Hatta International Airport, the Terminal Operation Center (TOC) Unit has played a good role in supervising operational and service performance in the Domestic Terminal 3 check-in area. This role is in accordance with applicable regulatory standards and Standard Operation Procedures (SOP).